2000
DOI: 10.1021/ic990931f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Square Planar Nickel(II)−Arylthiolate Complexes with the Biphenyl-2,2‘-dithiolate Ligand

Abstract: Two new NiIIS4 complexes with the biphenyl-2,2'-dithiolate ligand (L) are reported. The dinuclear complex 1, [Ni2L3]2-, was formed in the reaction of 2-3 equiv of Na2L and [NiCl4]2- and the mononuclear complex [NiL2]2- (2) by using 4-10 equiv of Na2L. Complexes 1 and 2 have been crystallographically characterized. (Et4N)2[1].0.5S2Ph2, CH3CN: C60H71N3Ni2S7, triclinic, P1, a = 13.806(2) A, b = 14.267(2) A, c = 16.873(2) A, alpha = 69.263(10) degrees, beta = 69.267(8) degrees, gamma = 83.117(10) degrees, Z = 2, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…As is typical for Mo(V) mono-oxo complexes, 1 is unreactive toward the oxygen atom acceptors DMS, PPh 3 , and PBu 3 for at least a week at ambient temperatures in solution. To the best of our knowledge, complexes with L are limited to 1, two square-planar nickel complexes [105], and a titanium system where the ligand was assembled on the metal center [106]. Malachowski and co-workers [107] have alkylated the thiolate sulfur atoms in L with imidazole-and pyridine-pendant groups to form tetradentate ligands.…”
Section: Resultsmentioning
confidence: 99%
“…As is typical for Mo(V) mono-oxo complexes, 1 is unreactive toward the oxygen atom acceptors DMS, PPh 3 , and PBu 3 for at least a week at ambient temperatures in solution. To the best of our knowledge, complexes with L are limited to 1, two square-planar nickel complexes [105], and a titanium system where the ligand was assembled on the metal center [106]. Malachowski and co-workers [107] have alkylated the thiolate sulfur atoms in L with imidazole-and pyridine-pendant groups to form tetradentate ligands.…”
Section: Resultsmentioning
confidence: 99%
“…Mono-and dinuclear nickel complexes have also been reported. [9] Rauchfuss et al [10] reported the synthesis of titanocene 2,2'-dithiolatobiphenyl by ring opening of dibenzothiophene with lithium metal followed by addition of sulfur and titanocene dichloride giving the final product from a salt-elimination reaction. Recently, our group has shown [11] that this complex can also be produced by oxidative addition of dibenzo [1,2]dithiin with titanocene dicarbonyl (Ti II ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that there are two kinds of metal ions in these two compounds, it is difficult to identify each transition here. We deduced that the former transition may be assigned to the d-d transition of nickel(II) ions, according to similar compounds in the literature [17,18].…”
Section: Magnetic Behaviormentioning
confidence: 68%